2022
DOI: 10.2147/ijgm.s341155
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Indicated Cervical Cerclage Efficacy Between 16 and 28 Weeks of Gestation in Twin Pregnancy: Retrospective Cohort Study

Abstract: The aim of this study is to determine if cervical cerclage administration reduces the preterm birth (PTB) rate at a gestational age (GA) of 16-28 weeks in women with twin pregnancy. Methods: This is a retrospective cohort study on asymptomatic twin pregnancy with an ultrasound-identified cervix length (CL) of ≦25 mm. The patients were divided into two groups: ultrasound-indicated cerclage (UIC) group and control (expectant management) group. The primary outcome was a PTB rate at <34 weeks. A logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In 2022, the RCOG suggested that ECC as a salvage measure in the case of premature cervical dilatation with exposed fetal membranes in the vagina can be considered in up to 27 +6 weeks of gestation 14 . Recently, some retrospective cohort studies indicated that ultrasound‐indicated cervical cerclage placement in twin pregnancies may dilate to 26 to 28 weeks of gestation 39,40 . In our study, the GA of ECC placement extended to 26 weeks.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In 2022, the RCOG suggested that ECC as a salvage measure in the case of premature cervical dilatation with exposed fetal membranes in the vagina can be considered in up to 27 +6 weeks of gestation 14 . Recently, some retrospective cohort studies indicated that ultrasound‐indicated cervical cerclage placement in twin pregnancies may dilate to 26 to 28 weeks of gestation 39,40 . In our study, the GA of ECC placement extended to 26 weeks.…”
Section: Discussionmentioning
confidence: 52%
“…14 Recently, some retrospective cohort studies indicated that ultrasound-indicated cervical cerclage placement in twin pregnancies may dilate to 26 to 28 weeks of gestation. 39,40 In our study, the GA of ECC placement extended to 26 weeks. Due to the small sample size, more large sample studies are needed to confirm this conclusion.…”
Section: Ta B L Ementioning
confidence: 88%
“…In addition, several retrospective casecontrol studies have been published. [71][72][73][74][75][76][77] In total, 969 women with twin pregnancies and TVUCL ≤ 25 mm have been evaluated in retrospective and prospective studies comparing cerclage versus no cerclage. Most of these studies conclude that there were no differences in GA at delivery or decreased PTB at different evaluated GAs or composite neonatal outcomes.…”
Section: Cervical Cerclagementioning
confidence: 99%
“…In addition, several retrospective case-control studies have been published 71–77 . In total, 969 women with twin pregnancies and TVUCL ≤25 mm have been evaluated in retrospective and prospective studies comparing cerclage versus no cerclage.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations did not allow the authors to reach evidence-based conclusions on the role of these interventions in reducing the risk of PTB in twin pregnancies. More importantly, in the last few years, an increasing number of studies reporting a potential beneficial role of cerclage in reducing the risk of PTB and adverse outcomes in twin pregnancies have been published [15][16][17][18][19][20]. These studies have challenged the prevailing view around the lack of effectiveness of cerclage in twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%